Teratogenic Effect of Carbamazepine Drug on the Histological Structure of Testes in the Albino Mouse (Mus musculus) - Thekra Atta Ibrahim1 , Mohammed Ali Mohammed2, Ibtisam Khalaf Abd ali3 , Mohammed Nsaif Abbs4 , Suaa (Indian Journal of Forensic Medicine & Toxicology, 2020)
The aim of this study was to evaluate the side effect of Carbamazepine on the histological structure of thetestis in white mouse males.A total of 24 male of Swiss white mice were divided into three groups, treated with Carbamazepine Drugfor (30) days. Within each treatment period, animals were assigned into three subgroups each of eight mice;control treated with vehicle and the others treated with 200, and 300mg/kg of Carbamazepine, The requireddose of the drug was dosed orally for all mice once per day for one month (30 days) for two concentrations.At the end of treatments, all mice were sacrificed; Testes was removed and weighed then kept in bufferedformalin solution for microscopic examination.The results of this study showed that animals that were injected with Carbamazepine caused a change in theshape and thickness of the wall of the somniferous tubules, where the appearance of the irregular, and alsoobserved the occurrence of an embolism in some germ cells and collected in the center of the cavity of thesomniferous tubules in addition to the observation of Vaculation and necrosis in most areas of somniferoustubules.The results of the current study suggested the possible time and dose-dependent disrupting potential ofCarbamazepine Drug on the Histological Structure of Testes in the Albino Mouse.